Mencegah Tindak Kekerasan pada Anak di Lembaga Pendidikan - Khaerul Umam Noer (Sawwa: Jurnal Studi Gender, 2019)
The role of Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A)—translated in English: the Integrated Service Center for the Empowerment of Women and Children— in the context of development is very important in order to oversee the government's steps in minimizing and handling cases of violence against women and children which are getting higher intensity from year to year, especially in educational institutions in the form of peer violence and violence by teacher. This study seeks to describe the collaboration of P2TP2A and the Education Office of Depok City in preventing violence against children in educational institutions. Observation and documentation studies are used as data collection techniques and qualitative descriptive analysis. This study produces findings including: 1) collaboration of P2TP2A and the Education Agency in the prevention of violence against children in the educational environment carried out in the form of socialization “Stop violence on children” and the establishment of children's Forums; 2) involvement of P2TP2A in the recruitment of teachers and principals. The form of collaboration still needs to be improved, especially in the preparation of hidden curriculum programs for handling violence, budgeting violence prevention activities for children in the school environment, and strengthening the authority of prevention until the handling of violence against women and children. This collaboration is at least a starting point that Depok becomes one of the regions that is highly committed in realizing Child Friendly Cities so that children's rights in the context of education can be fulfilled and the number of violence against children can be minimized.